Enhancing Diatom, Cyclotella meneghiniana growth using growth-promoting bacteria isolated from the phycosphere of chlorophytes and chrysophytes - Noor Mazli, Nur Amirah Izyan; Md Yusoff, Fatimah; Nazarudin, Muhammad Farhan; Khaw, Yam Sim; Tan, Hui Teng; Karim, Murni (Asian Fisheries Society, 2024)
The relationship between microalgae and bacteria in a microenvironment, the phycosphere, has a significant role in enhancing the quality and quantity of microalgal production, which would in turn affect consumers' growth and nutritional quality, such as the zooplankton, which are important live feeds in aquaculture. Thus, selecting and characterising suitable microalgal growth-promoting bacteria (MGPB) for enhancing microalgal production is an important process since not all bacteria promote high growth. In this study, physcosphere bacteria associated with chlorophytes and chrysophytes were isolated, screened for their microalgae-promoting attributes (phosphorus solubilisation, indole-3-acetic acid (IAA) production, and nitrogen fixation) and re-inoculated into microalgal cultures. A total of seven bacterial isolates were recorded to have multiple growth promoting traits, with three strains (CY-2, CY-4, CY-5) showing the greatest (P < 0.05) link for those traits. These seven potential MGPB were molecularly characterised using 16S rRNA approach. The phylogenetic tree of the isolated bacteria demonstrated the dominant bacteria associated with the chlorophytes were in the class bacteroidetes, while the chrysophytes appeared to be associated with Firmicutes bacteria suggesting that the compositions were strictly species-specific to the microalgae host. Enhanced Cyclotella meneghiniana growth by the seven isolated bacterial strains was highly dependent on the growth-promoting traits; especially those demonstrated by Pseudomonas hibiscicola and Ochrobactrum haematophilum. These two bacteria showed the potential to enhance the quality of microalgae, and they could be bioencapsulated and used to improve the quality of zooplankton as one of the main live feeds in the aquaculture industry. © Asian Fisheries Society.